2010
DOI: 10.1002/ange.200906054
|View full text |Cite
|
Sign up to set email alerts
|

Production of HCOOH/NEt3 Adducts by CO2/H2 Incorporation into Neat NEt3

Abstract: Research efforts are currently devoted to hydrogen storage in CO 2 as formic acid derivatives, a thirty-year old idea [1] not yet implemented. A chemical loop is conceivable based on a formate intermediate which can be produced in a pure and storable form under moderately high CO 2 and H 2 pressures and which can release gases at atmospheric pressure on demand when in contact with an appropriate catalyst. The catalytic decomposition of HCOOH itself has received renewed attention.[2] Remarkably, M. Beller and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Addition of small amounts of water or alcohols, as reported by Jessop, Noyori et al.,7 did not lead to significant improvement. Furthermore, the protocol of Fachinetti et al.,3k in which small amounts of formic acid salts were added as initiator in the NEt 3 system, was not successful in the case of NHex 3 as the sole solvent.…”
Section: Equilibrium Formic Acid Concentrations (Point Of Maximum Heamentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of small amounts of water or alcohols, as reported by Jessop, Noyori et al.,7 did not lead to significant improvement. Furthermore, the protocol of Fachinetti et al.,3k in which small amounts of formic acid salts were added as initiator in the NEt 3 system, was not successful in the case of NHex 3 as the sole solvent.…”
Section: Equilibrium Formic Acid Concentrations (Point Of Maximum Heamentioning
confidence: 99%
“…Many trialkylamines form formic acid rich liquid salts, which are not miscible with the free amine 3k. In these salts, only one equivalent of formic acid is deprotonated, whereas the excess (with respect to the amine) is presumably coordinated through hydrogen bonding.…”
Section: Equilibrium Formic Acid Concentrations (Point Of Maximum Heamentioning
confidence: 99%
“…known, the hydrogenation of CO 2 and the decomposition of formic acid are, except for a few studies, [26][27][28][29] usually reported independently.…”
Section: Introductionmentioning
confidence: 96%
“…In contrast to the direct reaction of H 2 with CO 2 , the hydrogenation of carbonate and bicarbonate are well-established reactions282930 that have been achieved in a wide variety of organic solvents, ionic liquids, water and supercritical CO 2 (ref. 20).…”
mentioning
confidence: 99%